HOMEOPATHIC MEDICINES-AAKASHMONI WILL BE THE BEST VACCINE AGAINST COVID-19: ENRICHING AGRICULTURE SCIENCE AND TECHNOLOGY COMMUNICATION MECHANISM APPLICATION ISSUES! - Datta, Subhas Chandra (International Journal of Research -GRANTHAALAYAH, 2020)
Still now, no effective vaccine or treatment for the fifth endemic novel coronavirus COVID-19, forming endemic, is analogous to war, affecting our normal-, private- and professional- life, the planet economy, and also the communities. It is reported from the previous experiments, the homeopathic biomedicines; Aakashmoni or Acaciasides, or Acacia auriculiformis-extract, is being employed traditionally to beat various medical complications. Present pretreatment with ultra-high-diluted homeopathic biomedicine-Aakashmoni, prepared from the fruits of acacia A. Cunn, mixed with water at a particularly low dose, were applied by foliar spray once daily for 15 days @ 10 ml/plant, against present, root-knot-, leaf spot-, powdery mildew-, mosaic- and tukra- mulberry diseases, during a field trials and silkworms rearing. Pretreatment- investigations have confirmed that ultra-high-diluted homeopathic biomedicine Aakashmoni highly effective in ameliorating different mulberry diseases by inducing their natural defense-response against pathogens-infection and leaving no residual toxicity within the leaves to affect the expansion of silkworms also. Presently, no appropriate antiviral drugs are discovered to treat COVID-19. So, to concur matters, “Four Confirmed-Suggestions for Vaccine and Clinical Trials with Homeopathic Biomedicines-Aakashmoni at an especially low dose, Against COVID-19 at by Boosting system for the development of Science and Technology Communication Mechanism Application Issues” forming the ‘Best Vaccine’, which not only shows the clinical, physical, chemical, biological and physiological effects but also on relative molecular mass, explaining the confirmation of mechanism and action of the homeopathic medicines supported scientific experimentations and proofs, and also the future clinical-scientists develop all aspects of clinical-case-reports globally by publishing with the sincere hope that the crisis of human civilization will soon be over and also the whole world may retain in normal forms by fighting against the COVID-19 war.